Adjustment of Early Aged Children with Language Disorder - Kharisma Hakiki; Farida Kurniawati (Fakultas Psikologi Universitas Pancasila, 2020)
The purpose of this literature review is to describe the adjustment of early aged children with language disorder. Through the ProQuest and EBSCO electronic databases with publication dates between October 2009 and October 2019, 4 relevant articles were obtained. Based on the results of the analysis, it was found that early childhood with language disorder has an unfavorable adjustment which is characterized by the presence of several problems related to adjustment, namely the discovery of behavioral and learning problems, difficult temperaments and self regulation problems. Gender and mother's education level is one of the factors that can influence language development in children. Systematic instruction using feedback can be used to teach early childhood academic and social skills with language disorder in small group settings. Book reading context is found to be able to develop vocabulary. In addition, toy play was found to produce a more balanced speech ratio than reading books. Various problems related to adjustment are experienced by early aged children with language disorders. External or environmental factors are expected to provide support for children to achieve good adjustment, especially in young children who have language disorders.